PELAYANAN DINAS PERDAGANGAN DALAM PENGATURAN PERIZINAN PEMAKAIAN TEMPAT DASARAN PEDAGANG PASAR MANGKANG DI KOTA SEMARANG (Faculty of Law, University of Palembang, 2023)
Management of the Semarang Mangkang Market is regulated in the Semarang City Regional Regulation based on Number 9 of 2013 concerning Traditional Market Arrangements. The Department of Trade has the authority to operate markets for the benefit of the people of Semarang City. The purpose of this study is to find out how the services of the Department of Commerce are in arranging permits for the use of the food stalls for Pasar Makang traders in the city of Semarang, knowing what are the inhibiting factors and efforts in arranging permits for the use of the places for the traders of the Mangkang Market in the city of Semarang. The research method used in this research is normative juridical (legal research), using primary data as supporting data and secondary data as the main data, the specifications of this research are analytical descriptive, the data collection method uses interview techniques and library research, data analysis uses the qualitative. Factors that influence the fulfillment of permit issuance for traders who have not obtained a permit to use the basis of the base are as follows: Limited land owned by the Mangkang Market, Lack of understanding from traders on the importance of the Permit to Use the basis of the Makang market traders in Semarang City has been carried out in accordance with regulations Regional Number 9 of 2013 concerning Traditional Market Arrangements, but the implementation of services at the Mangkang Market in Semarang City has not been fully optimal, there are still some traders who still do not have a permit to use a basic place.